Experiments to modify grape juice potassium content and wine quality on granite derived soils near Paardenberg - Agenbach, G. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Soil Science))--University of Stellenbosch, 2006.